Development Of Basic Science Concept Modules From The Perspective Of The Qur'an At Uin Ar-Raniry - Azhar, Azhar (Lembaga Penelitian dan Pendidikan Mandala, 2025)
To improve the effectiveness of the learning process, innovative learning strategies can be implemented, such as changing the routine in using learning resources. The innovation in this research is the development of a learning module on basic science concepts based on the Quran, with the hope that students in Aceh, where Islamic law is practiced, will be more motivated in the learning process and thus improve their learning outcomes. The purpose of this study is to determine the feasibility of the basic science concept learning module developed from the perspective of the Qur'an, the responses of students and teaching staff in the field of study to the basic science concept learning module from the perspective of the Qur'an, and the influence of the basic science concept learning module from the perspective of the Qur'an on student learning outcomes. This study applies a research and development design, which is a research design applied to produce and develop a product and to test the effectiveness of the resulting product. The results of this study indicate that mlongThe learning of basic science concepts from the perspective of the Qur'an that was developed is suitable for use in the process of teaching basic science concepts, the response of students and teaching staff at UIN Ar-Raniry is positive.waybasic concepts of science from the perspective of the Qur'an, as well as mlongThe learning developed was declared effective in improving the learning outcomes of UIN Ar-Raniry students in learning basic science concepts.